Combining live fluorescence imaging with in situ cryoelectron tomography sheds light on the septation process in Deinococcus radiodurans - Lorenzo Gaifas; Jean-Philippe Kleman; Françoise Lacroix; Erin Schexnaydre; Jennyfer Trouve; Cecile Morlot; Linda Sandblad; Irina Gutsche; Joanna Timmins (Proceedings of the National Academy of Sciences, 2025)
Cell division is a fundamental biological process that allows a single mother cell to produce two daughter cells. In walled bacteria, different modes of cell division have been reported that are notably associated with distinctive cell shapes. In all cases, division involves a step of septation, corresponding to the growth of a new dividing cell wall, followed by splitting of the two daughter cells. The radiation-resistant Deinococcus radiodurans is a spherical bacterium protected by a thick and unusual cell envelope. It has been reported to divide using a distinctive mode of septation in which two septa originating from opposite sides of the cell progress with a flat leading edge until meeting and fusing at mid-cell. In the present study, we have combined conventional and superresolution fluorescence microscopy of live bacteria with in situ cryogenic electron tomography of bacterial lamellae to investigate the septation process in D. radiodurans . This work provides important insight into i) the complex architecture and multilayered composition of the cell envelope of this bacterium, ii) the unusual “sliding doors” septation process and iii) the sequence of events and molecular mechanisms underlying septal closure, including the synthesis of a FtsZ-dependent peptidoglycan layer that rigidifies and straightens the growing septa.